Case report: Late-onset hypertrophic pyloric stenosis in a 3-year-old boy: It is never too late - Iacoviello, Onofrio; Verriello, Giuseppe; Castellaneta, Stefania; Palladino, Stefano; Wong, Michela; Mattioli, Girolamo; Giordano, Paola; Francavilla, Ruggiero; Cristofori, Fernanda (Frontiers in Pediatrics, 2022)
Hypertrophic Pyloric Stenosis (HPS) represents a relatively rare occurrence beyond infancy. Here we present the case of an almost 3-years-old boy diagnosed with late-onset HPS and successfully treated with extra-mucosal pyloromyotomy. We review the literature, challenging the principle that more aggressive surgical approaches, should be preferred over less invasive ones.